Accounting for Multiple Comparisons in Statistical Analysis of the Extensive Bioassay Data on Glyphosate. (19th March 2020) - Crump, Kenny; Crouch, Edmund; Zelterman, Daniel; Crump, Casey; Haseman, Joseph
Abstract: Glyphosate is a widely used herbicide worldwide. In 2015, the International Agency for Research on Cancer (IARC) reviewed glyphosate cancer bioassays and human studies and declared that the evidence for carcinogenicity of glyphosate is sufficient in experimental animals. We analyzed 10 glyphosate rodent bioassays, including those in which IARC found evidence of carcinogenicity, using a multiresponse permutation procedure that adjusts for the large number of tumors eligible for statistical testing and provides valid false-positive probabilities. The test statistics for these permutation tests are functions of p values from a standard test for dose-response trend applied to each specific type of tumor. We evaluated 3 permutation tests, using as test statistics the smallest p value from a standard statistical test for dose-response trend and the number of such tests for which the p value is less than or equal to .05 or .01. The false-positive probabilities obtained from 2 implementations of these 3 permutation tests are: smallest p value: .26, .17; p values ≤ .05: .08, .12; and p values ≤ .01: .06, .08. In addition, we found more evidence for negative dose-response trends than positive. Thus, we found no strong evidence that glyphosate is an animal carcinogen. The main cause for the discrepancy between IARC's finding and ours appears to be that IARC did not account for the large number of tumor responses analyzed and the increased likelihood that several of these would show statistical significance simply by chance. This work provides a more comprehensive analysis of the animal carcinogenicity data for this important herbicide than previously available.